Role of type I interferon in the bacillus Calmette-Guérin-induced expression of CXCL10 from human monocytes. Issue 5 (2004) - Samperio, Patricia Méndez; Trejo, Artemisa; Miranda, Elena
Abstract : BACKGROUND : The proinflammatory chemokine CXCL10, in addition to its chemotactic properties, is also involved in the stimulation of natural killer and T-cell migration in Mycobacterium tuberculosis infection. In this study, our experiments were designed to determine the role of interferon (IFN)-αβ in the production of CXCL10 by human monocytes infected with Mycobacterium bovis bacillus Calmette-Guérin (BCG). Methods : The concentrations of CXCL10 in culture supernatants of monocytes infected with M. bovis BCG were determined by enzyme-linked immunosorbent assay. CXCL10 mRNA levels were determined by the reverse transcription-polymerase chain reaction method. Results : We have shown the induction of CXCL10 following infection with M. bovis BCG in a dose-dependent and time-dependent manner. Importantly, the secretion of CXCL10 in response to M. bovis was increased by IFN-α. These results were further confirmed by the fact that the addition of an anti-IFN-αβ neutralizing antibody completely reversed the stimulatory effect, whereas an isotype-matched control antibody had no significant effect on CXCL10 secretion. It is important to note that no significant effect of type I IFN on CXCL8 production in M. bovis -infected monocytes was observed. This was consistent with the finding by the reverse transcription-polymerase chain reaction method that treatment with anti-IFN-α/β antibodies potentially inhibited CXCL10 mRNA levels, whereas no significant effect was observed on CXCL8 mRNA. Moreover, in THP-1 monocytes and THP-1 macrophages, the addition of exogenous IFN-α stimulated CXCL10 secretion. Conclusions : Collectively, these results indicate that the type I IFN may play an important role to modulate the expression of CXCL10 in M. bovis BCG infection. Studies on M. bovis -induced chemokine secretion could provide important insight into the regulation of the immune response against tuberculosis.